Kant and Hippel – Civility as a Value - Miodoński, Leon (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
This article deals with the comparative approach of two philosophers of the German Enlightenment Immanuel Kant and Theodor Gottlieb von Hippel in the context of socio- political issues, primarily civil society, civil rights, and civility. The article consists of three parts. First part – presentation of the era of Frederick II, in particular the concept of state reform, the formation of bourgeois consciousness and the role of Freemasonry. The second part focuses on the semantic analysis of the notion of “citizen” and the question of the change that took place at the end of the eighteenth century, namely the transition from the original meaning of “city dwelling” to a political and legal meaning. Kant’s practical philosophy takes up this theme. The third part is devoted to the analysis of the concept of “citizen” and the conditions and prospects for the development of civil society in the philosophy of Kant and Hippel. Hippel’s concept can be considered secondary to Kant’s. Nevertheless, both approaches – Kant’s and Hippel’s – grow out of the spirit of the age, the expectation of change, the prospect of a better world to come.